Abiotic Environment Predicts Micro- but Not Macroevolutionary Patterns of Flower Color in Monkeyflowers (Phrymaceae) - Grossenbacher, Dena; Makler, Leah; McCarthy, Matthew; Fraga, Naomi (Frontiers in Plant Science, 2021)
Anthocyanin pigments are responsible for many of the vivid pink, purple, red and blue flower colors across angiosperms, and frequently vary within and between closely related species. While anthocyanins are well known to influence pollinator attraction, they are also associated with tolerance to abiotic stressors such as extreme temperatures, reduced precipitation, and ultraviolet radiation. Using a comparative approach, we tested whether abiotic variables predict floral anthocyanin in monkeyflowers (Phrymaceae) across western North America. Within two polymorphic species we found that abiotic variables predicted flower color across their geographic ranges. In Erythranthe discolor, the frequency of pink flowered (anthocyanin producing) individuals was greater in populations with reduced precipitation. In Diplacus mephiticus, the frequency of pink flowered individuals was greater at higher elevations that had reduced precipitation and lower temperatures but less ultraviolet radiation. At the macroevolutionary scale, across two parallel radiations of North American monkeyflowers, species with floral anthocyanins (pink, purple, or red corollas) occupied areas with reduced precipitation in Erythranthe but not Diplacus. However, after accounting for phylogenetic relatedness, we found no evidence for the joint evolution of flower color and environmental affinity in either clade. We conclude that although abiotic stressors may play a role in the evolution of flower color within polymorphic species, we found no evidence that these processes lead to macroevolutionary patterns across monkeyflowers.